A Study on Tidal Potential and Tide Generating Force - Rahman, M Mizanur; Paul, Gour Chandra; Hoque, Ashabul (GANIT: Journal of Bangladesh Mathematical Society, 2018)
This study deals with the derivation of tidal potential and tide generating forces. Tidal potential is derived from the gravitational attraction of masses of the moon and the sun and from this potential tide generating forces are derived taking its horizontal gradients. GANIT J. Bangladesh Math. Soc.Vol. 37 (2017) 29-37